Effect of hydrothermal aging on the physical, optical and mechanical properties of an experimental 3Y/4Y zirconia bilayer system - Marun, Manoela Médola (2024)
The aim of this study was to synthesize an experimental bilayer zirconia comprised by second-generation 3Y-TZP and ultra-translucent 4Y-PSZ, and to characterize and compare its microstructure, optical, and mechanical properties before and after hydrothermal aging with its monolithic counterparts (3Y-TZP and 4Y-PSZ). Disc-shaped specimens (ISO 6872:2015) were obtained by uniaxial pressing of commercial powders (Zpex and Zpex4; Tosoh Corporation). The samples were sintered at 1550°C for 2 hours and divided into three groups: bilayer 3Y/4Y, monolithic 3Y, and monolithic 4Y. Half of the samples of each group were subjected to aging in a hydrothermal reactor for 20 hours at 2.2 bar and 134°C. Both bilayer surfaces and monolithic specimens were characterized using scanning electron microscopy (SEM), X-ray diffraction (XRD) and Raman spectroscopy. Optical properties were determined by the contrast ratio (CR) and translucency parameter (TP). Mechanical properties were assessed by biaxial flexural strength. XRD evidenced monoclinic phase after aging with contents of 66%, 32%, 66%, and 40% for 3Y (bilayer), 4Y (bilayer), 3Y (control), and 4Y (control), respectively. Raman spectra presented monoclinic content on the aged surface of 87%, 45%, 87%, and 47% for 3Y (bilayer), 4Y (bilayer), 3Y (control), and 4Y (control), respectively. SEM exhibited dense and homogeneous microstructure with smaller grains in bilayer groups, unaffected by aging. Hydrothermal aging did not influence TP and CR, regardless of the system. Monolithic 3Y demonstrated lower TP and higher CR compared to 4Y bilayer and monolithic groups. Aging increased the characteristic strength of all groups. Fractographic marks indicated the origin of fracture and direction of crack propagation from tensile side defects to the compression surface. Hydrothermal aging triggered alterations in the crystalline content, microstructure, and mechanical properties of the experimental bilayer zirconia system as well as of their monolithic controls.